Wearable Non-Invasive Arterial Pulse Detection with a Millimeter-wave Radar - Bahmani, Nima; Salami, Dariush; Yigitler, Huseyin; Hietala, Juhapekka; Panula, Tuukka; Sigg, Stephan (United States, 2026)
Cardiovascular diseases remain a leading cause of mortality and disability. The convenient measurement of cardiovascular health using wearables is a key enabler to foster continuous, accurate and early detection, diagnosis and management of cardiovascular diseases. We integrate Photoplethysmography (PPG) and mmWave sensing in a mobile wearable device to detect the Inter-beat interval (IBI) and arterial pulse wave. Particularly, We have developed a hardware prototype that integrates both sensing modalities and have verified the system against the gold clinical standard reference with a diverse population of 23 subjects.
ISWC '25: Proceedings of the 2025 ACM International Symposium on Wearable Computers